How does COVID-19 affect r*? - Jakob Feveile Adolfsen; Thea Thalia Iuel Rasmussen; Jesper Pedersen (Danmarks Nationalbank, 2020)
This memo discusses effects of COVID-19 on interest rates through the lens of global movements in the natural real interest rate. While government spending and public debt issuance are likely to cause a rise in r*, r* may decline due to precautionary behaviour. The net effect is uncertain.
Keywords: 330; Realzins; Coronavirus; Wirkungsanalyse; Theorie; Welt